Agricultural Crop Damage Pests and their Modeling - kizi, Botiralieva Maftuna Botirali (European Journal of Life Safety and Stability (2660-9630), 2022)
This article provides complete information about pests of agricultural crops, types of pests, biological effects on agricultural crops, and mathematical modeling for pest identification.